'You're kicking me out?' Scansion and the variable-length session in Lacanian clinical praxis. Issue 2 (2nd April 2016) - Pietrusza, Celeste; Hook, Derek
Abstract : This paper tackles the Lacanian topics of scansion and the variable-length session, drawing both on existing literature and on two short case studies. Scansion – the clinical procedure of punctuating, interrupting or cutting a patient's analytical productions – is discussed in view of a key historical precedent within psychology, namely the notion of the Zeigarnik effect. It is, furthermore, briefly related to Freud's work (his treatment of the Wolf Man, the technique of free association) before being clinically contextualised via attention to the Lacanian diagnostic structures of neurosis, psychosis and perversion. Fragments of two cases – one focused on an obsessive and another on a hysterical patient – are offered as a means of introducing a more clinically applied description of scansion. This mode of intervention – akin to an enigmatic interpretative gesture – aims to put the unconscious to work; to disrupt the defensive productions of the ego; and to, potentially, extend and support the transference. The paper concludes by noting that while the conventional 50-min session provides a secure, regular and containing space within which patients may speak, what it forecloses are the prospective therapeutic benefits related to the effects of interruption and suspension, separation and non-resolution.